Analysis of Marketing Margin and Efficiency to Enhance the Welfare of Argopuro Coffee Farmers in Jember Regency, Indonesia - Dian Galuh Pratita; Apip Gunaldi Dalimunthe; Vivi Annisa (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
The agricultural sector plays an essential role in the Indonesian economy, particularly in generating foreign exchange, creating employment opportunities, and supplying raw materials for the food and beverage processing industry and the agro-industry. Coffee has long been cultivated by the community of Jember Regency, especially in Pace Village. Argopuro coffee is promoted as a flagship variety and has become an icon of Jember Regency. This study focuses on the specific context of Argopuro coffee in Jember Regency, which has distinct geographical, social, and marketing characteristics compared to other coffee-producing regions. Specifically, this study aims to analyze the marketing margins and marketing efficiency of coffee in the Suka Maju Gapoktan in Pace Village, Jember Regency. This region-based approach enables a more context-specific and applicable analysis of the conditions local farmers face. This study was conducted on 74 coffee farmers who are members of the Suka Maju Farmers Group Association (Gapoktan) located in Pace Village. The importance of coffee as a commodity forms the background of this research. A quantitative research method was applied to calculate marketing margins and marketing efficiency. The study involved coffee farmers within the Suka Maju Gapoktan. The results indicate that the marketing margin is IDR1.000. The marketing channels are considered efficient, with efficiency levels of 8.84% for ground coffee and 7.10% and 7.62% for green coffee beans. This study contributes to improving the efficiency of the coffee marketing system.